Composites from Recycled and Modified Woods Technology, Properties, Application - Reinprecht, Ladislav; Iždinský, Ján (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recycled woods obtained from old buildings, furniture, industrial products, etc., as well as from modified woods prepared by thermal, chemical, or biological processes, have the potential to be a base or complementary raw material for construction and decorative wood composites used mostly in buildings, furniture, and for transport. Typical construction composites are glued prisms and boards (e.g., glulam, blockboard), glued large-area boards from veneers (e.g., plywood, laminated veneer lumber), or large-area boards from wood particles and fibers (e.g., particleboard, oriented strand board, medium-density fiberboard). More of the large-area boards can obtain a better decorative function usable in furniture and building architecture after veneering, lamination, coating, plasma-treating or other surface-treating technologies.Within this Special Issue, selected articles related primarily to wood composites prepared from recycled and modified woods are presented with a focus on the type and properties of used raw materials, additives, and technological processes, including finishing and surface treatments, with an impact on the resulting properties and service-life of wood composites in different use scenarios.